PENGARUH RELIGIUSITAS TERHADAP PERILAKU BERAMAL (CHARITABLE BEHAVIOR) MASYARAKAT KOTA YOGYAKARTA - Sri Maulida (JESI (Jurnal Ekonomi Syariah Indonesia), 2013)
Abstract The aim of this research is to know the effect of religiosity on charitable behavior at the society of Yogyakarta City. The charitable behavior in this research is the concept from Islam paradigm e.g. Zakat, Infak, Sadaqah and Waqf. This research is field research by using a quantitative approach. The population of this research is all people at Yogyakarta City. It used judgment sampling method with a sample of 100 Moslem respondents at Yogyakarta City, and it used simple regression techniques to analyze the data. Variables such as religiosity, intrinsic religiosity, extrinsic religiosity and Islamic doctrine are studied by their potency to influence the charitable behavior at Yogyakarta. Keywords: religiosity, charitable behavior.